Genre and the performance of publics - Reiff, Mary Jo, editor; Bawarshi, Anis, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
Moves beyond institutional settings to explore public contexts that are less hierarchical, broadening the theory of how genres contribute to the interconnected and dynamic performances of public life. Extends the understanding, not only social ways of organizing texts or mediating relationships within institutions, but dynamic performances themselves.--Provided by publisher.
Genre as interdiscursive performance in public space / Vijay K. Bhatia -- In between genres: uptake, memory, and U.S. public discourse on Israel-Palestine / Anis Bawarshi -- Disambiguating "uptake": toward a tactical research agenda on citizens' writing / Dylan B. Dryer -- Defining moments: genre beginnings, genre invention, and the case of the English language dictionary / Lindsay Rose Russell -- Geographies of public genres: navigating rhetorical and material relations of the public petition / Mary Jo Reiff -- Bodily scripts, unruly workers, and public anxiety: scripting professional embodiment in interwar vocational guides / Risa Applegarth -- Uncovering occluded publics: untangling public, personal, and technical spheres in jury deliberations / Amy J. Devitt -- Discourse coalitions, science blogs, and the public debate over global climate change / Graham Smart / Multiple intertextual threads and (un)likely uptakes: an analysis of a Canadian public inquiry / Tosh Tachino -- Appropriating genre, "taking action" against obesity: the rhetorical work of digital genre systems in public discourse / Monica Brown -- Exigencies, ecologies and internet street science: genre emergence in the context of Fukushima radiation risk discourse / Jaclyn Rea and Michelle Riedlinger -- Spreadable genres, multiple publics: the pixel project's digital campaigns to stop violence against women / Jennifer Nish.
Keywords: Literary form; Rhetoric -- Political aspects; Rhetoric -- Social aspects